The impact of new drug launches on hospitalization in 2015 for 67 medical conditions in 15 OECD countries: a two-way fixed-effects analysis - Frank R. Lichtenberg (Center for Economic Studies and ifo Institute (CESifo), 2019)
There are two types of prescription drug cost offsets. The first type of cost offset—from prescription drug use—is primarily about the effect of changes in drug quantity (e.g. due to changes in out-of-pocket drug costs) on other medical costs. The second type of cost offset—the cost offset from prescription drug innovation—is primarily about the effect of prescription drug quality on other medical costs. Two previous studies found that pharmaceutical innovation reduced hospitalization, and that the reduction in hospital cost from the use of newer drugs was considerably greater than the innovation-induced increase in pharmaceutical expenditure. In this study, we reexamine the impact that pharmaceutical innovation has had on hospitalization, employing a different type of 2-way fixed effects research design. We estimate the impact that new drug launches that occurred during the period 1982-2015 had on hospitalization in 2015 for 67 diseases in 15 OECD countries. Our models include both country fixed effects and disease fixed effects, which control for the average propensity of people to be hospitalized in each country and from each disease. The number of hospital discharges and days of care in 2015 is significantly inversely related to the number of drugs launched during 1982-2005, but not significantly related to the number of drugs launched after 2005. (Utilization of drugs during the first few years after they are launched is relatively low, and drugs for chronic conditions may have to be consumed for several years to achieve full effectiveness.) The estimates imply that, if no new drugs had been launched after 1981, total days of care in 2015 would have been 163% higher than it actually was. The estimated reduction in 2015 hospital expenditure that may be attributable to post-1981 drug launches was 5.3 times as large as 2015 expenditure on those drugs.
Keywords: I10; L65; O33; 330